2018
DOI: 10.14336/ad.2018.1110
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1292 Targets FZD4 to Regulate Senescence and Osteogenic Differentiation of Stem Cells in TE/SJ/Mesenchymal Tissue System via the Wnt/β-catenin Pathway

Abstract: With the expansion of the elderly population, age-related osteoporosis and the resulting bone loss have become a significant health and socioeconomic issue. In Triple Energizer (TE)/San Jiao (SJ)/mesenchymal tissue system, mesenchymal stem cell (MSC) senescence, and impaired osteogenesis are thought to contribute to age-related diseases such as osteoporosis. Therefore, comprehending the molecular mechanisms underlying MSC senescence and osteogenesis is essential to improve the treatment of bone metabolic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 75 publications
0
43
0
Order By: Relevance
“…Blocking myostatin (a ligand that binds to members of the TGF-ß superfamily) by the application of follistatin increased the osteogenic potential of adipose-derived stem cells (Wallner et al, 2019). The micro-RNA 1292 (a regulator of Wnt/β-catenin pathway) inhibited osteoblastic differentiation and increased the senescence of human adipose-derived MSCs in vitro and promoted ectopic bone formation in vivo (Fan et al, 2018). The micro-RNA146a-5p was expressed in CD14 + monocytes, and this expression was correlated with differentiation into osteoclasts and with bone resorption in patients (Lin et al, 2019).…”
Section: Targetsmentioning
confidence: 99%
“…Blocking myostatin (a ligand that binds to members of the TGF-ß superfamily) by the application of follistatin increased the osteogenic potential of adipose-derived stem cells (Wallner et al, 2019). The micro-RNA 1292 (a regulator of Wnt/β-catenin pathway) inhibited osteoblastic differentiation and increased the senescence of human adipose-derived MSCs in vitro and promoted ectopic bone formation in vivo (Fan et al, 2018). The micro-RNA146a-5p was expressed in CD14 + monocytes, and this expression was correlated with differentiation into osteoclasts and with bone resorption in patients (Lin et al, 2019).…”
Section: Targetsmentioning
confidence: 99%
“…In vivo MSC senescence implies reduced osteogenic capacity, thus contributing to age-related diseases such as osteoporosis. In ASCs, miR-1292 was found to positively regulate cell senescence through the wingless-related integration site (Wnt)/β-catenin signalling pathway and targeting frizzled 4 receptor (FZD4), thus emerging as a potential target to treat osteoporosis [117]. Moreover, Liu et al [118] demonstrated that the loss of osteogenic potential in aged BM-MSCs is mediated by p53 increase through the miR-17 pathway.…”
Section: In Vivo Msc Senescencementioning
confidence: 99%
“…Meanwhile, TGF-β accelerated cellular senescence by promoting the miR-29-mediated loss of H4K20me3. Fan et al [65] observed the role of miR-1292 in cellular senescence of human adipose-derived mesenchymal stem cells (hADSCs). They found that FZD4 downregulation acted as a potential target of miR-1292, leading to overexpression of miR-1292, which promoted hADSC aging and osteogenic differentiation.…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%